SUMO unloads the Kap114 cab - Werner, Andreas; Melchior, Frauke (The EMBO journal, 2012)
Nucleocytoplasmic transport is an essential mechanism in all eukaryotic cells, for which the basic mechanisms seemed well understood. Transport receptors of the importin b/karyopherin family recognize, translocate and discharge cargo. Key to directed transport is the GTPase Ran, which determines compartment-specific interactions between receptors and their cargo. In this issue of The EMBO Journal, Rothenbusch et al (2012) now add a new energy-dependent event to this basic pathway by providing direct evidence that the posttranslational modification of the yeast import receptor Kap114 with small ubiquitin-related modifier (SUMO) is indispensable for its correct function. An exciting model emerges in which Kap114 sumoylation regulates Ran-dependent cargo release, and thereby acts as a mechanism for intranuclear targeting of the import cargo.
Gesehen am 31.08.2018